A PERCEPÇÃO DA QUALIDADE DE VIDA NO TRABALHO EM PERÍODO PÓSAQUISIÇÃO DE EMPRESA DE TELECOMUNICAÇÕES UM ESTUDO DE CASO NO BRASIL - Costa, Michele de Abreu Martins R. da (2009)
The dissertation aims to determine whether and how the employees quality of working life is affected after a recent acquisition process between two private mobile telecommunications companies. Thus, a case study was the technique chosen. The research instrument was a questionnaire applied in the post-merger, to the employees from two similar boards in the prior companies. Frequency and types of perceptions were compared for these two groups and the co-existence of qualitative and quantitative approaches contributed to collect essential data to reach the objectives of the research. Finally it was concluded that the quality of working life is affected by processes of acquisition and the acquired company is the most adversely affected. The employees of this company perceived negative effects manly on working conditions, opportunities for growth and safety and in the personal life. For the purchasing company, the largest negative impact occurred in the workload. In the resulting company, most of the staff realized the decrease in individual performance and productivity in the post-acquisition phase. As a potential contribution, this study highlights the importance of post-acquisition phase in the employees quality of working life.